Análise transcriptômica da interação mamoeiro-Papaya Meleira Virus - Madroñero, Leidy Johana (2014)
Papaya is one of the fruit crops most cultivated in tropical and subtropical regions. Brazil is a major producer and exporter of papaya in the world. The largest area in Brazil, about 70%, for producing papaya is located in Espiritu Santo and Bahia. However this production is affected by infectious diseases caused by pathogens. The sticky disease caused by Papaya meleira virus (PMeV) is one of the most sever diseases. Not resistance has been reported for sticky disease and interestingly their symptoms only are triggered at the ripening. The molecular mechanisms involved in both the symptoms’ development and in the papaya defense response are still unclear. To understand the key point in this pathosystem leading to purpose crops genetic improvement methodologies we conducted a transcriptomics study. Rna-seq technology was used to sequencing the transcriptome from PMeV inoculated and no inoculated plants with 3, 6 and 8 months old. The differentially expressed genes in the both conditions and in the three times were found. Using different graphics analysis we show the global gene expression patterns in this interaction. We found 21 genes exhibit an altered profile at six month just in the inoculated condition. 8 genes related with defense response like cellular death and stress responses and biotic and abiotic stimulus were down regulated whereas 13 genes involved with primary metabolic process, biogenesis, cell differentiation, cell cycle, cell communication, cell grown, well as in reproduction and flower development were up regulated. This results suggest that in the six month the plant is forced to change their gene expression program routed to response for the physiological processes involved just at this period and should this is being favored over the stress response leading to the symptoms development.